Experiences addressing health-related financial challenges with disease management among African American women with asthma. (June 2014) - Patel, Minal R.; Caldwell, Cleopatra H.; Id-Deen, Effat; Clark, Noreen M.
Abstract Objective: Despite economic hardship, compliance with self-management regimens is still evident among individuals and families managing chronic disease. The purpose of this study was to describe how women with asthma address cost-related challenges to management of their condition. Methods: In 2012 and 2013, four focus groups were conducted in Southeast Michigan with 26 African American women with asthma, recruited based on maximum variation sampling procedures. A semi-structured interview protocol was employed by trained facilitators. Coded transcripts were analyzed for themes regarding means to reduce the impact of the cost of asthma management. Results: Major themes identified were acceptance of the status quo; stockpiling and sharing medicines; utilizing community assistance programs; reaching out to healthcare providers and social networks for help; foregoing self-management; and utilizing urgent care. Conclusions: Awareness of strategies that are helpful to patients in reducing out-of-pocket costs may better equip service providers and others to develop interventions to make useful strategies more widely available.